WHITE DRAGON FRUIT (Hylocereus undatus) POTENTIAL AS DIABETES MELLITUS TREATMENT - Ajie, Rizky Bayu (Majority, 2015)
Abstract Diabetes mellitus is a metabolic disorder that affects many people in the world. Diabetes mellitus is characterized by high levels of glucose in the blood due to lack of insulin secretion, insulin action or both. Many countries elaborate herbal compounds that have the efficacy for decreasing blood glucose levels such as white dragon fruit (Hylocereus undatus). Substances in the white dragon fruit most instrumental in decreasing blood sugar levels is a flavonoid that has three working mechanism in decreasing blood sugar levels such as decrease oxidative stress, inhibit the intestinal mucosa GLUT 2 and inhibit phosphodiesterase. White dragon fruit has the effect of decreeasing blood sugar levels in patients with diabetes mellitus. Keywords: blood glucose level, flavonoid, herbal, Hylocereus undatus Abstrak Diabetes Diabetes melitus merupakan gangguan metabolik yang mengenai banyak orang di dunia. Diabetes melitus ditandai dengan tingginya kadar glukosa dalam darah akibat kurangnya sekresi insulin, kerja insulin maupun keduanya. Banyak negara mengembangkan senyawa herbal yang memiliki khasiat menurunkan kadar glukosa darah seperti buah naga putih (Hylocereus undatus). Zat didalam buah naga putih yang yang paling berperan dalam menurunkan kadar gula darah adalah flavonoid yang mempunyai tiga mekanisme kerja dalam menurunkan kadar gula darah yaitu menurunkan stress oksidatif, menghambat GLUT 2 mukosa usus dan menghambat fosfodiesterase. Buah naga putih memiliki efek menurunkan kadar gula darah pada pasien dengan diabetes melitus. Kata kunci : flavonoid, herbal, Hylocereus undatus, kadar glukosa darah